Prioritization of solid concentration and temperature for solid state anaerobic digestion of pearl millet straw employing multi-criteria assessment tool - Kunwar Paritosh (Nature Portfolio, 2019)
Abstract India produces huge quantities of agricultural residues and stubbles and mainly disposed by burning on site causing air pollution. The organic matter present in the residues and stubble may be utilized by anaerobic digestion as a source of renewable energy subsequently reducing emission of greenhouse gases caused by burning. In the present study, solid state anaerobic digestion (SSAD) of pearl millet straw was investigated at mesophilic and thermophilic temperature with four different total solid (TS) content (15, 20, 25 and 30%). Results showed that 20 and 25% TS generated maximum methane (124.1 ± 7 and 162.4 ± 9L/kg VS) at mesophilic and thermophilic temperature respectively. However, increasing TS content beyond 25% did not show significant increment on methane yield. Analytical analysis showed correlation between the reduction of volatile solids and methane yield as well as VFA (volatile fatty acid) accumulation at high TS content. Also, VlseKriterijuska Optimizacija Komoromisno Resenje (VIKOR) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) methods as MultiCriteria Decision Making modelling (MCDM) applied to select best possible alternative for SSAD of pearl millet. MCDM analysis showed that VIKOR method endorsed the experimental results.